2006
DOI: 10.1016/j.ejso.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of sentinel node biopsy and stage migration of breast cancer

Abstract: Aim: The purpose of this study was to examine in a large population based group of breast cancer patients treated in a regular care setting whether the introduction of the Sentinel Node Biopsy (SNB) led to detection of a higher percentage of patients with positive regional lymph nodes. Methods: The study includes 3665 early breast cancer patients, aged 30e85 years, diagnosed in the period 1997-2002 and registered at the Regional Cancer Registry of the Comprehensive Cancer Centre Middle Netherlands. During this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 18 publications
0
21
1
1
Order By: Relevance
“…Furthermore, we included patients diagnosed over a longer period of time and compared two periods before and after introduction of the SNB. Remarkably, despite the availability of a national guideline regarding SNB, our study showed a smaller increase in number of micrometastases than the report from the central part of The Netherlands [21]. The most likely explanation for this discrepancy is a difference in the thoroughness of the examination of the SN between pathology laboratories, with a varying number of sections and cutting intervals.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, we included patients diagnosed over a longer period of time and compared two periods before and after introduction of the SNB. Remarkably, despite the availability of a national guideline regarding SNB, our study showed a smaller increase in number of micrometastases than the report from the central part of The Netherlands [21]. The most likely explanation for this discrepancy is a difference in the thoroughness of the examination of the SN between pathology laboratories, with a varying number of sections and cutting intervals.…”
Section: Discussioncontrasting
confidence: 54%
“…A recent study from the Comprehensive Cancer Centre Middle Netherlands showed that the percentage of patients diagnosed with positive lymph nodes increased from 30% in 1997 to 40% in 2002 [21]. This increase could be entirely explained by the increasing proportion of patients with micrometastatic disease, which rose from 1% to 10%.…”
Section: Discussionmentioning
confidence: 92%
“…Occult metastases or micrometastases were detected in 9-23% of originally Hematoxylin & Eosin node-negative cases [8]. Recent studies showed a 4.3-10% increase among patients diagnosed with micrometastatic disease in the sentinel node as well [9,10]. This increase led to stage migration after adjustment for the simultaneous, favorable trend in tumor size [9].…”
Section: Introductionmentioning
confidence: 99%
“…Strength of SLNB technique over ALND is its careful and precise evaluation of few specimen by intensive methods as serial sectioning and ImmunoHistoChemistry (IHC) to detect more micrometastasis as well as isolated tumor cells (Lyman et al, 2005). Although detection of nodepositive patients considerably rises at least 10% after introduction of SLNB procedure (van der Heiden-van der Loo et al, 2006), however, importance of these cells and probable effect on outcome and treatment planning is a controversial issue (Cox et al, 2008;Langer et al, 2009;TruongLesperance, 2010)and requires to be answered in ongoing clinical trials as ACOSOG -Z0010 and IBCSG-23-01 (Giuliano et al, 2011;Galimberti, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…So, many extensive histopathologic examination of SLN has been designed to identify micrometastases and isolated tumor cells and even molecular changes (Lyman et al, 2005). Some studies show that detection of metastasis by SLNB technique is better than ALND and percentage of node-positive patients considerably rises at least 10% after introduction of SLNB procedure (Lyman et al, 2005;Mansel et al, 2006;van der Heiden-van der Loo et al, 2006) and is largely explained by watchful lymphatic mapping.…”
Section: Value Of Sentinel Lymph Node Biopsy In Breast Cancermentioning
confidence: 99%